Application of Micro-Raman Spectroscopy to the Study of Yttria-Stabilized Tetragonal Zirconia Polycrystal (Y-TZP) Phase Transformation - Ramos, Carla MüeIler; Tabata, Américo Sheitiro [UNESP]; Cesar, Paulo Francisco; Rubo, José Henrique; Fracisconi, Paulo Afonso Silveira; Borges, Ana Flávia Sanches (Soc Applied Spectroscopy, 2015)
The aim of this study was to perform micro-Raman spectroscopy as an alternative and nondestructive method to identify the phase transformation of zirconia after mechanical stress. The groups evaluated were experimental zirconia, zirconcad, IPS e.max ZirCad, and In Ceram YZ. Ten specimens were constructed for each group (n = 30) and subjected to a three-point bending test with a crosshead speed of 0.5 mm/min. The fractured surfaces were analyzed by micro-Raman spectroscopy. The laser power was kept at 10 mW, and scanning was performed in three regions of the fractured surface: (i) near the source of the failure (region of tensile stress), (ii) central to the fractured surface, and (iii) far from the source of failure. All materials showed the characteristic bands of tetragonal and monoclinic phases of zirconia. All zirconia studied showed a monoclinic phase in the tensile stress region. Micro-Raman spectroscopy was effective in detecting the presence of crystalline phases in polycrystals ceramics.
Keywords: Zirconia; Phase transformation; Micro-Raman spectroscopy